2020
DOI: 10.1111/andr.12757
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of erectile function by suppression of corporal apoptosis and oxidative stress with losartan in aged rats with erectile dysfunction

Abstract: Background:The prevalence of erectile dysfunction (ED) increases progressively with age, but its potential pathophysiology has not been fully demonstrated. Hence, this article was aimed to identify the functional and morphological characterization of the corpus cavernosum in aged rats and to evaluate the effects of the Angiotensin II type 1 receptor antagonist losartan on age-related ED (AED). Material and Methods:A total of 40 young and aged Sprague Dawley rats were randomly divided into four groups (n = 10 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 43 publications
(44 reference statements)
1
7
0
Order By: Relevance
“…The above process depends on the normal function of the endothelial cells and smooth muscle cells (3). Several studies have reported that the phosphorylation of AKT and eNOS in the penis of aged rats is decreased (23,24). In the present study, our results indicated that PI3K/AKT and eNOS/ NO/cGMP pathways were downregulated in the aged rats, and this downregulation was accompanied by endothelial dysfunction.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The above process depends on the normal function of the endothelial cells and smooth muscle cells (3). Several studies have reported that the phosphorylation of AKT and eNOS in the penis of aged rats is decreased (23,24). In the present study, our results indicated that PI3K/AKT and eNOS/ NO/cGMP pathways were downregulated in the aged rats, and this downregulation was accompanied by endothelial dysfunction.…”
Section: Discussionsupporting
confidence: 64%
“…Fibrosis, resulting from diabetes and nerve damage, is also involved in the pathophysiological process of ED (7,25). The process of fibrosis has also been reported to be involved in aging-related ED (18,23). Fibrosis in penile tissue often involves a decrease in the content of cells, such as smooth muscle cells, an increase in the content of collagen, and the fragment and decrease of elastic fibers (26).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress has been causatively linked to ED pathogenesis resulting from a variety of pathologies, including obesity, type 2 diabetes, and aging [ 37 , 38 , 39 , 40 ]. While the penile vasculature represents a unique circulatory system that is predominantly maintained in a low perfusion (flaccid) state primarily by α-adrenergic-mediated vasoconstriction [ 41 ], studies utilizing endothelial cell culture or arteries of the central circulation may provide insights into molecular functioning that may have potential relevance to ED pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the etiology of age-related ED has been explored from different perspectives to support future clinical transformation. Wang et al [ 8 ] found that increases in apoptosis, fibrosis, and oxidative stress (OS) occurred in rats with age-related ED and may be the targets of losartan. Bragina et al [ 9 ] found that the renin-angiotensin system (RAS) is involved in age-related ED and that the activity of the ACE-Ang II-AT1 axis in the CC is enhanced, which is positively correlated with fibrosis and inflammation of the CC.…”
Section: Introductionmentioning
confidence: 99%